Intercultural communication - Lê, Văn Thanh (Giáo dục Việt Nam, 2014)
This book introduction to culture and inter - cultural communication, marking introductions, verbal communication, niverbal communication, frienships, family values, educational attitudes, cultural conficts, cultural adjusment.